Diversification of weeds in clearfield rice (MR220 CL2) planting system / Maslinda Ramli - Ramli, Maslinda (Faculty of Plantation and Agrotechnology, 2019)
Rice, Oryza sativa is the staple food in Malaysia as the people in the country mostly consumed rice as their daily food source. However, the presences of weed infestation in the rice field have caused reduction in rice production. Knowledge of weeds presence in rice field is crucial thing as it can help in deciding on how to control and formulate correctly the herbicide solution to be applied. In order to control the weeds presence in the rice field, the diversification of weeds presence in the Clearfield rice planting system was studied. The focus of the study are to identify the distribution of weed and also to study the most dominant and pervasive weeds in the rice field. The study was carried out on the rice field located at Jalan Othman, Bukit Lintang, Malacca by using quadrat method. A total of 20 quadrats with 0.5m×0.5m size were used. The area of 2.5 acre was observed with W inverted pattern. The total of weed population observed was 550 comprising of eight species from six different families (Leptochloa chinensis, Echinochloa crus-galli, Eclipta prostrata, Utricularia flexuosa, Monochoria vaginalis, Ludwigia hyssopifolia, Cyperus difformis, Fimbristylis globulosa). The result shows that the higher type of weed frequency in the rice field is Monochoria vaginalis (80%) which present in most of quadrats observed while the highest density of weed in the rice field is Cyperus difformis (37.2m2) which abundantly present in the cluster.